Cell Lung Cancer Proliferation Downregulation by Tanshinone IIA: A Systematic Review and Meta-analysis - Farzad Amiri; Anahita Shirvani; Majid Hajizadeh; Mahsa Hajizadeh; Negar Eghbalifard; Fatemeh Rabiee (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Background and aim: The current investigation was carried out to ascertain the efficacy of Tan IIA in treating both non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). Material and methods: To obtain documentation and scientific evidence for the effectiveness of Tan IIA on small cell lung cancer cells articles published in international databases such as PubMed, Web of Science, Scopus, Sites Direct, Elsevier, Wiley, and the search engine Google Scholar were used. Data were analyzed using STATA software, version 17. Effect size with 95% confidence interval (CI), random effects model, and REML method were used. Results: Seven studies were examined. Tanshinone IIA treatment downregulated SCLC proliferation by 4.8 percent (ES: 4.8 95 percent CI -0 point61, 1 point56). Results indicate that Tanshinone IIA treatment decreased NSCLC cell migration (ES: 6.2 percent, 95 percent confidence interval [CI], 1.01). Conclusions: According to the current study, tanshinone IIA can inhibit the growth of both SCLC and NSCLC. Therefore, it may be regarded as a therapeutic option for both.